Treatment technologies of fresh market wastewater - Jais, N. M.; Miswan, M. S.; Radin Mohamed, Radin Maya Saphira; Al-Gheethi, A. A. (Springer Nature, 2020)
Fresh Market Wastewater (FMWW) is rich with high amounts of suspended solids, organic and inorganic compounds, nutrients, gases and some elements which come from ﬁsh entrails and seafood preparation sales, meat cutting, poultry slaughtering, fruits and vegetables sales. The excess of these parameters are harmful to the aquatic life since the FMWW is usually discharged into the drainage systems without any treatment or partial treatment. The FMWW technologies are developed due to some technical factors inﬂuencing the designation and construction. There are several projects of fresh market treatment technologies used on site area in small scale which could be replicated to other fresh market, and some case study have been tested in laboratory batch experiments. All the projects exhibited an efﬁciency to reduce critical parameters in FMWW and give positive impacts to the locals and responsible parties.